1997
DOI: 10.1080/016502597385144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Northern Irish Children’s Attitudes to War and Peace Before and After the Paramilitary Ceasefires

Abstract: This study compares the attitudes of young people in Northern Ireland to con ict and con ict resolution, before and after the 1994 cease re announcements. Content analysis on the responses of 117 adolescents aged 14-15 years showed differences in their attitudes to war and peace and in their strategies to attain peace. Concepts of war as static and unchanging showed a signi cant difference after the cease re. In addition, the perception of war as a struggle between national leaders before the cease re shifted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Downloaded by [University of Toronto Libraries] at 13:54 26 November 2014 76 Ferguson The significant increase in the level of just world beliefs after the bilateral paramilitary ceasefires suggests that the possibility of hope offered by the cessation of violence and the structural changes during this time presented the adolescents of Northern Ireland with an opportunity to view a more impartial just society on the horizon. McLernon et al (1997) also found similar changes in attitudes after the 1994 ceasefires, with a significant shift in Northern Irish adolescents seeing peace as an absence of war to viewing peace in terms of universal rights, freedom and equality.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Downloaded by [University of Toronto Libraries] at 13:54 26 November 2014 76 Ferguson The significant increase in the level of just world beliefs after the bilateral paramilitary ceasefires suggests that the possibility of hope offered by the cessation of violence and the structural changes during this time presented the adolescents of Northern Ireland with an opportunity to view a more impartial just society on the horizon. McLernon et al (1997) also found similar changes in attitudes after the 1994 ceasefires, with a significant shift in Northern Irish adolescents seeing peace as an absence of war to viewing peace in terms of universal rights, freedom and equality.…”
Section: Discussionsupporting
confidence: 58%
“…Contemporary research has suggested that encountering a period of hope after living in a community suffering sustained political conflict and injustice may have a positive effect on psychological attributes. Qouta, Punamaki and El Sarraj (1995) have examined the impact of the Israeli-Palestinian peace treaty on the psychological well-being of Palestinian children, while McLernon, Ferguson and Cairns (1997) studied the effect of the Northern Irish paramilitary ceasefires on adolescent attitudes to war and peace. Qouta et al found that the peace treaty between Israel and the Palestine Liberation Organisation (PLO) had a positive influence on psychological well-being via a decrease in neuroticism, concluding that "historical and political changes do, indeed, influence psychological dynamics" (Qouta et al 1995).…”
Section: -1031 )mentioning
confidence: 98%
“…To assess children's understanding of enemies and enemy images, the methods of free association, drawing, and interview were used. These methods have been used successfully in the assessment of enemy images in previous studies (Hesse & Poklemba, 1989; Hesse & Mack, 1991; Povrzanovic, 1997), as well as conceptions about peace and war (McLernon & Cairns, 2001; Rudenberg, Jansen, & Fridjhon, 1998; Punamaki & Suleiman, 1990). The free association method requires participants to respond with the first words that come to mind to a target word that is embedded in a series of neutral words.…”
mentioning
confidence: 99%
“…It was to be expected that their experience of psychological stress would be higher than the students who experienced 18 months of living in peace. 4,14 The aim of the work presented here was to examine psychological stress in two cohorts of clinical dental students in 1992 (during the troubles) and 1995 (during the cease-®re of 1994±96).…”
Section: Discussionmentioning
confidence: 99%